2017
DOI: 10.1186/s12885-017-3577-x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of immune cells, low tumor proliferation and wild type BRAF mutation status is associated with a favourable clinical outcome in stage III cutaneous melanoma

Abstract: BackgroundThe variable prognosis in stage III cutaneous melanoma is partially due to unknown prognostic factors. Improved prognostic tools are required to define patients with an increased risk of developing metastatic disease who might benefit from adjuvant therapies. The aim was to examine if cellular immune markers in association with tumor proliferation rate and BRAF mutation status have an impact on prognosis in stage III melanoma.MethodsWe have used two sets of case series with stage III disease: 23 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Neutrophils and Macrophages M1 are related to radiation therapy. Our data further validated these findings from the previous studies that specific immune cells were related to predicting clinical outcome (3537).…”
Section: Discussionsupporting
confidence: 91%
“…Neutrophils and Macrophages M1 are related to radiation therapy. Our data further validated these findings from the previous studies that specific immune cells were related to predicting clinical outcome (3537).…”
Section: Discussionsupporting
confidence: 91%
“…The former up-regulated processes are involved in the enhancement of cell proliferation and are linked to malignancy of cancer [ 33 ], which means the poor survival of WT Bf-CM predicted by this signature might be resulted from the more malignant behavior in cancer biology. This was supported by a retrospective study which concluded that low tumor proliferation rate was significantly associated with a better prognosis [ 45 ]. Moreover, in spite of the removal from sub-classification of thin melanomas in recent the AJCC staging system [ 46 ], mitotic rate can still be a significant prognostic indicator especially for WT Bf-CM.…”
Section: Discussionmentioning
confidence: 72%
“…To date, immune checkpoint blockage therapy has been recommended for the treatment of advanced WT Bf-CM [ 47 ]. Additionally, the infiltration of immune cells can both serve as the predictor of responses to checkpoint therapy and WT Bf-CM survival [ 45 , 48 , 49 ]. However, little differences in immune infiltration was observed in the WT Bf-CM patients between high- and low- risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…The former up-regulated processes are involved in the enhancement of cell proliferation and are linked to malignancy of cancer 32 , which means the poor survival of WT Bf-CM predicted by this signature might be resulted from the more malignant behavior in cancer biology. This was supported by a retrospective study which concluded that low tumor proliferation rate was signi cantly associated with a better prognosis 44 . Moreover, in spite of the removal from sub-classi cation of thin melanomas in recent the AJCC staging system 45 , mitotic rate can still be a signi cant prognostic indicator especially for WT Bf-CM.…”
Section: Discussionmentioning
confidence: 82%
“…To date, immune checkpoint blockage therapy has been recommended for the treatment of advanced WT Bf-CM 46 . Additionally, the in ltration of immune cells can both serve as the predictor of responses to checkpoint therapy and WT Bf-CM survival 44,47,48 . However, little differences in immune in ltration was observed in the WT Bf-CM patients between high-and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%